Prevalence of Autoimmune Gastritis in Individuals Undergoing Medical Checkups in Japan - Notsu, Takumi (Intern Med, 2019)
OBJECTIVE: Based on both endoscopic findings and serum auto-antibody levels, we determined the prevalence of autoimmune gastritis (AIG), which has not been previously reported, in individuals who underwent health checkup examinations in Japan. METHODS: At total of 6,739 subjects (4,288 males, 2,451 females; mean age 52.1 years) underwent an upper gastrointestinal endoscopic examination as part of an annual medical checkup. Those suspected to have AIG based on endoscopic evidence of proximal-predominant gastric mucosal atrophy were further examined for the presence of anti-parietal cells and anti-intrinsic factor antibodies, with a final diagnosis of AIG made in cases found to be positive for either or both of those factors. RESULTS: Of the 6,739 examined subjects, 46 were suspected to have AIG based on the endoscopic findings, of whom 33 were finally diagnosed with AIG, for an overall prevalence 0.49% (females 0.65%, males 0.40%). Seven with AIG also had thyroid disease, including Hashimoto's and Basedow disease, while none with AIG showed anemia in blood test findings. The prevalence of AIG was not different regardless of the H. pylori infection status (negative, positive, post-eradicated). CONCLUSION: In individuals who underwent an upper gastrointestinal endoscopic examination as part of an annual checkup in Japan, the prevalence of AIG was 0.49%. We concluded that it is not uncommon for asymptomatic and healthy individuals to have AIG, and propose that additional studies are needed to clarify its prevalence as well as to establish the criteria used for diagnosis.